an investigation into the semantics of the english verb “get” and the vietnamese verbs “lấy, nhận” - Huỳnh Thị Thanh Vân (Trường Đại học Ngoại ngữ, 2025)
The thesis “An Investigation into the Semantics of the English verb ‘Get’ and the Vietnamese verbs “Lấy,” “Nhận” (in terms of the Semantic Categories of “Acquiring,” “Obtaining” and “Receiving”)” aims to help learners thoroughly understand the differences and similarities on semantic features of these verbs to make the effective use of them.